Protein determination of "Kuhol" (Ampullaria cuprinos) at different age levels and the survey of its use as feed supplement for ducks - Barrido, Nenita
The study has two components, namely, the laboratory and community extension components. The first component was limited to the quantitative determination of crude protein in golden "kuhol" at different age levels and a comparison of the physical properties of the meat obtained. The second component extended the technology to the nearby barangays.A modified Kjeldahl method utilized by Lake, et. Al. (1951) was used to determine the nitrogen content of samples. It was observed that the color and texture of the meat at different age levels were all the same. They were tender, creamy, slippery, juicy and had a golden brown color. Some parts of it were black and red. The shells were thin, soft, smooth and golden brown in color. The result of the study showed that a 3-month old golden "kuhol" had the highest crude protein content, 67.16 percent, followed by a 4-month old, 59.83 percent, and then by a 2-month old having a value of 49.86 percent. Statistical analysis using t-test further revealed that the percentage crude protein content of golden "kuhol" at the age of three months was significantly higher (p<0.01) compared to the percentage crude protein content of golden "kuhol" at the ages of two and four months. similarly when comparison was made in the percentage of crude protein content of golden " kuhol" with ages of two and four months, a highly significant difference was obtained. This means that the percentage crude protein content of golden "kuhol" was significantly higher in four months than in two months. Generally in this research the percentage crude protein content of golden "kuhol" was highest at the age of three months and lowest at the age of two months. The second component of the study is the community outreach. The surrounding barangays were surveyed for the purpose of determining the status of "kuhol" among communit dwellers of Barnagays Acuit, Cabilauan Monpon, Agcuyawan Calsada and Agcuyawan Pulo. Said dwellers were encouraged to put up ponds for "kuhol" raising. "kuhol" raising in the aforementioned barangays was extensively practiced. The "kuhol" raisers are at the same time duck and tilapia raisers. All the "kuhol" raisers got the same results when "kuhol" was used as feed supplement to their ducks. They had substantial gains when "kuhol" was given to their ducks as feed supplement. Based on the findings of the study, it is recommended that golden "kuhol" be used as feed supplement for ducks and tilapia to reduce feed cost. Likewise, it is strongly recommended that golden "kuhol" (3 months old) be used as feed supplement for poultry.. A study on feed formulation incorporatng meat of golden "kuhol" maybe undertaken for commercial purposes.Furthermore, a similar study should be conducted to show trend of protein content as "kuhol" matures. This would mean the determination of protein content of five, six, seven, etc. month old "kuhol".